Welcome to Scribd, the world's digital library. Read, publish, and share books and documents. See more
Download
Standard view
Full view
of .
Save to My Library
Look up keyword
Like this
2Activity
0 of .
Results for:
No results containing your search query
P. 1
Una Solución al ejercicio Nº 40 de CALCULUS de Tom M Apostol

Una Solución al ejercicio Nº 40 de CALCULUS de Tom M Apostol

Ratings: (0)|Views: 211 |Likes:

More info:

Published by: Emmanuel Pedroza Niño on Dec 15, 2010
Copyright:Attribution Non-commercial

Availability:

Read on Scribd mobile: iPhone, iPad and Android.
download as PDF, TXT or read online from Scribd
See more
See less

06/12/2014

pdf

text

original

 
Una soluci´on al problema N
o
40 del LibroCALCULUS de Tom M. Apostol
Emmanuel Pedroza Ni˜noDecember 14, 2010
El ejercicio consiste en calcular la siguiente integral:
∫ 
2
x
x
2
x
2
dx
(1)Racionalizando el numerador de la expresi´on se tiene:
∫ 
2
x
x
2
x
2
dx
=
∫ 
2
dxx
2
2
x
x
2
  
∫ 
dxx
2
x
x
2
  
φ
∫ 
dx
2
x
x
2
  
ξ
El problema (1) se transform´o en el c´alculo de las integrales Ω,
φ
y
ξ
De Ω se tiene:
∫ 
2
dxx
2
2
x
x
2
= 2
∫ 
dxx
2
√ 
2
(
x
2
+
x
+
14
) +
14
= 2
∫ 
dxx
2
√ 
94
(
x
+
12
)
2
Tomando la sustituci´on
x
+
12
=
32
sin
k
,
dx
=
32
cos
k dk
,
x
2
=(3sin
k
1)
2
4:= 2
∫ 
32
cos
k dk
(3sin
k
1)
2
4
√ 
94
94
sin
2
k
= 8
∫ 
dk
(3sin
k
1)
2
1
 
Aplicando la sustituci´on
t
= tan
k
2
, dk
=2
dt
1 +
t
2
,
sin
k
=2
t
1 +
t
2
se obtienede Ω : 8
∫ 
2
dt
1+
t
2
(
6
t
1+
t
2
1
)
2
= 16
∫ 
1 +
t
2
(6
t
1
t
2
)
2
.Descomponiendo en fracciones simples:16
∫ 
1 +
t
2
(6
t
1
t
2
)
2
= 16
∫ 
dtt
2
6
t
+ 1+ 96
∫ 
tdt
(
t
2
6
t
+ 1)
2
= 16
∫ 
dt
(
t
3)
2
8+ 96
∫ 
t dt
[(
t
3)
2
8]
2
Tomando la sustituci´on
t
3 = 2
2sec
r, dt
= 2
2sec
r
tan
rdr
:Ω = 16
∫ 
2
2sec
r
tan
rdr
8sec
2
r
8+ 96
∫ 
(2
2sec
r
+ 3)2
2sec
r
tan
rdr
64(sec
2
r
1)
2
= 4
2
∫ 
sec
r
tan
rdr
+128
∫ 
(2
2sec
r
+ 3)2
2sec
rdr
tan
3
r
= 4
2
∫ 
csc
rdr
+ 12
∫ 
cos
rdr
sin
3
r
+ 9
2
∫ 
csc
r
cot
2
rdr
= 4
2ln
|
csc
r
cot
r
|
6sin
2
r
9
22sin
2
r
+
= 4
2ln
t
3
2
2
t
2
6
t
+ 1
6
t
2
6
t
+ 1(
t
3)
2
9
22(
t
2
6
t
+ 1)(
t
3)
2
= 4
2ln
t
3
2
2
t
2
6
t
+ 1
12 + 9
22
(
t
3)
2
t
2
6
t
+ 1+
2
 
= 4
2ln
tan
k
2
(3 + 2
2)
2
2ln
(
tan
k
2
3
)
2
8
12 + 9
22
(tan
k
2
3)
2
(tan
k
2
3)
2
8= 4
2ln
2
x
+ 13 + 2
2
x
x
2
(3 + 2
2)
2
2ln
2
x
+ 13 + 2
2
x
x
2
3
2
8
12 + 9
22
2
x
+ 13 + 2
2
x
x
2
3
2
2
x
+ 13 + 2
2
x
x
2
3
2
8+
De
φ
se tiene:
∫ 
dxx
2
x
x
2
=
∫ 
dxx
 
94
(
x
+
12
)
2
Haciendo la sustituci´on
x
+
12
=
32
sin
k
,
dx
=
32
cos
k dk
se obtiene:
φ
=
∫ 
32
cos
k
(3sin
k
1)2
√ 
94
94
sin
2
k
=
∫ 
2
dk
3sin
k
1Tomando la sustituci´on
t
= tan
k
2
, dk
=2
dt
1 +
t
2
,
sin
k
=2
t
1 +
t
2
, se tiene:
φ
=
∫ 
4
dt
1+
t
2
6
t
1+
t
2
1=
4
∫ 
dtt
2
6
t
+ 1=
4
∫ 
dt
(
t
3)
2
8Por ´ultimo, haciendo la sustituci´on
t
3 = 2
2sec
r, dt
= 2
2sec
r
tan
rdr
:
φ
=
4
∫ 
2
2sec
r
tan
rdr
8(sec
2
r
1)=
2
∫ 
sec
r
tan
rdr
=
2
∫ 
csc
rdr
=
2ln
|
csc
r
cot
r
|
+
Finalmente se tiene:
ξ
=
∫ 
dx
2
x
x
2
=
∫ 
dx
 
94
(
x
+
12
)
2
3

Activity (2)

You've already reviewed this. Edit your review.
1 thousand reads
1 hundred reads

You're Reading a Free Preview

Download
/*********** DO NOT ALTER ANYTHING BELOW THIS LINE ! ************/ var s_code=s.t();if(s_code)document.write(s_code)//-->